The Commitment of Nineveh Governorate Residents to the Precautionary Measures against Global 2019 Pandemic and Dermatological Affection of Precautions - Baraa A. Al-Rahawe; Abdulsattar Abdullah Hamad; Mohanad H. Al-Zuhairy; Hameed Hasan Khalaf; Solomon Abebaw (Applied Bionics and Biomechanics)
The world has changed dramatically since the novel pandemic pours in all aspects of life, including economic, health, and social life. The first case was initially observed in the Wuhan province of China; fast spread occurs around the world. Until now, there is no proven effective treatment for it. The study’s objectives are to assess residents of Nineveh governorate’s commitment to the COVID-19 pandemic precautionary measures recommended by the WHO and Iraqi national authorities; the protective measures are used to prevent its spread and restrict the viral infectivity. Several cutaneous changes were observed in some persons as a result of prolonged contact with personal protective equipment and excessive use of personal hygiene measures.